PENELITIAN KUALITAS AIR BENGAWAN SOLO PADA SAAT MUSIM KEMARAU - Sukmawati Rahayu (JURNAL SUMBER DAYA AIR, 2009)
The Bengawan Solo which flows through Central and East Java is the largest river in Java Island, and itswater is used for various activities such as agriculture, fishery, domestic use, irrigation, and waterresources for drinking water. Based on a research carried out in upstream Bengawan Solo, water qualityshows a decline indicated by the decrease of dissolved oxygen and increase of BOD and COD. At locationGrogol, dissolved oxygen ranges between 4.4 7.9 mg/L and decreases at Kemiri to 0 6.4 mg/L. BOD atGrogol shows a range between 1.3 4.5 mg/L increasing to 4.8 8.1 mg/L at Kemiri. COD range between3.7-13 mg/L at Grogol increases to 12 30 mg/L at Kemiri. In downstream Bengawan Solo, at locationNapel and Babat, water quality indicates an increase indicated by increase of dissolved oxygen, anddecrease ofBODand COD. The increasing dissolved oxygen and decreasingBODandCODin downstreamarea shows that the self purification process is happening in the river. The Fecal coli form bacteria at eachlocation is found very high and beyond criteria.